Pancreatic Lymphangioma: A Rare Case Report - Ahmet Gökhan Sarıtaş; Figen Doran; Kıvılcım Erdoğan; Abdullah Ülkü; Uğur Topal; Hakan Karataş (Haseki Tıp Bülteni, 2019)

(untitled)
Intraabdomınal lymphangioma is a rare disease. Pancreatic counterpart occurs as cystic mass and should be kept in mind in patients with cystic pancreatic lesions. It is important to diagnose preoperatively to choose therapy modality. In this paper, we present a rare case of pancreatic lymphangioma which was diagnosed incidentally